Polanyi and Schumpeter vs. Neoliberalism: Can Neoliberal World Be Explained by Schumpeter in the Context of Innovation and Polanyi in the Context of the Market? - Akansel, Ilkben (Handbook of Research on Managerial Thinking in Global Business Economics, 2019)
Neoliberalism means “new liberalism.” It could be dated back to 18th century, but it is a term that belongs today. Since 1990, neoliberal rules gave many harmful effects, especially to developing countries, and those harmful effects have proceeded for labor class. As capitalism stands on its own feet, it can find solutions to regain profits. However, the concern may well be gaining too much profit gives harmful effects on a wide range of social classes. Neoliberalism is accepted as the tool of these effects by the majority of the economists. In this chapter, the authors scrutinize the consequences of neoliberalism by the mediation of two great philosophers who criticized capitalism in different ideas. Karl Polanyi's and Joseph A. Schumpeter's different opinions about capitalism will be scrutinized in order to understand the connection between capitalism and neoliberalism. So, in this study, starting with its name, neoliberalism's implementations will be scrutinized by two great philosophers
Keywords: business economics; neoliberalism

Economic and Political Foundations of Effective Transition to Renewable Energy: Ordoliberalism, Polanyi, and Cities as Hubs for Climate Leadership and Innovation - Lysack, Mishka (Renewable Energy: International Perspectives on Sustainability, 2019)
A remarkable transition to a renewable energy economy (also known as the Energiewende) with ambitious climate protection and sustainable economic development is taking place in Germany, with many German cities exemplifying best practices in effective climate leadership to attain ambitious climate goals, such as Munich (1.4 million) moving steadily to its targets of 100% renewable energy by 2025 and 100% renewable heat by 2040. Similarly, the former coal city of Bottrop in West Germany won the Innovation Ruhr Prize for increasing its refurbishment rate to 3% (3× national average), installing solar panels, reducing its GHG emissions by 37%, and attracting over $316 million in economic investment in sustainability. However, it needs to be noted these accomplishments do not take place in a vacuum, but within a supportive and empowering policy and economic context which includes two key elements. The first entails using Karl Polanyi’s three key analytic resources of restoring the social and environmental dimensions of the economy: (1) re-embedding the economy within society and in turn, within the larger context of the environment, (2) reversing the reduction of labour and land into “fictitious commodities” and tradable goods; and (3) fostering the “double movements” of the protective responses of both government and society to correct the negative impacts of the free-market economy. Secondly, the economic approach of ordo-liberalism in Germany facilitates the shift to an economy with economic rules and “referees,” fostering the renewable energy transition through innovative economic and social capital approaches, while also deconstructing the economic monopolies and concentrations of political-economic power that arise in neo-liberal and authoritarian economies.
Keywords: double movement; fictitious commodities; ordoliberalism; reembedding; renewable energy economy; sustainability

Correlated ownership: Polanyi, Commons, and the property continuum - Frerichs, Sabine; James, Rick (Research Handbook on the Sociology of International Law, 2018)
According to the economic analysis of law, an efficient property regime is premised on the universality, the exclusivity, and the transferability of property rights. Ideally then, every (legal) person can enjoy the status of an owner and any (economic) resource can become private property; ownership titles could be bought and sold across national jurisdictions and would ultimately be respected everywhere in the world. Throughout history, property regimes indeed seem to have moved towards this ideal. However, this conception of private property is far less natural than it seems, and not without problems. Instead, the institution of property rights is inherently connected with the development of capitalist society, and it reflects the latter’s underlying tensions. The starting point for a sociological account of property rights is to conceive them as a social relation, or a relation of power, which includes (other) owners and non-owners as well as the state as a ‘third party’. In this chapter, the authors build on the work of Karl Polanyi and John R. Commons to suggest that the property regime of the market society relies both on the reification of property (identifying it with the thing owned) and the commodification of the right of ownership (turning it into a marketable commodity). Looking back, the authors retrace how the concept of property changed with the advent of modern capitalism, and how it evolved in the transition from agricultural to industrial capitalism. Looking into the future, they also address the challenges of today’s informational capitalism, which is characterized by the commodification of knowledge. Based on James’s work, the authors introduce the ‘correlative rights doctrine’ as an alternative to the remnant ‘property rights absolutism’ in the field of intellectual property law, but also beyond. With cross-border conflicts in who owns what having proliferated in the global age, investigations into the relational quality of property rights also matter for international lawyers, who are confronted with new subjects and objects of property, from international investment law to intellectual property law.
Keywords: COMMONS, J.R.; international law; property rights

Markets in West Africa: Karl Polanyi, or what sort of social formation - Saul, Mahir (Market as Place and Space of Economic Exchange: Perspectives from Archaeology and Anthropology, 2018)
Keywords: West Africa; disembeddedness; economic anthropology; economic history; markets

Karl Polanyi vs Friedrich von Hayek: The Socialist Calculation Debate and Beyond - Dale, Gareth (Hayek: A Collaborative Biography: Part XIV: Liberalism in the Classical Tradition: Orwell, Popper, Humboldt and Polanyi, 2018)
It is well known that Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation were written contemporaneously (between 1940 and 1943), that their authors propounded antithetical political ideologies (right-wing liberalism and left social democracy respectively), and that the two books revolve around a similar problematique: the causes of the collapse of liberal order in the interwar era. This chapter undertakes a detailed comparison of Hayek and Polanyi’s Weltanschauung (including ethics, economic analysis, and political perspectives). It reveals a chequered picture, in which diametrically opposed political views articulate with points of striking agreement in economic analysis. This helps to explain the manner in which certain Polanyian theses, notably on the ‘constructed’ market order and the ‘spontaneous’ social-movement response, appear to mirror those of Hayek.
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Polanyi; constructed market order; history of economic thought; liberalism; methodology; socialist calculation debate

Summoning Hunger: Polanyi, Piers Plowman, and the Labor Market - Epstein, Robert (Money, Commerce, and Economics in Late Medieval English Literature, 2018)
The “plowing of the half-acre” episode in Langland’s Piers Plowman includes a chilling passage in which Piers summons Hunger to force able but unwilling laborers to work the land. This chapter approaches the episode by way of the economic history of Karl Polanyi, whose critiques of free-market ideology are receiving renewed attention in the context of globalization and the international economic crisis. One of Polanyi’s key points is that the threat of starvation is a prerequisite to the institution of a true labor market—meaning that first the networks of collective support that peasants rely on for survival need to be undermined. The summoning of Hunger shows that Langland is actually more free market in his ideology than are the landowning supporters of the labor statutes.
Keywords: LANGLAND, William; Piers Plowman (book); economic history; globalization; hunger; threat of starvation

The State in Classical Laissez-Faire, Its Crisis, and the Establishment of Fordism - Bonanno, Alessandro (The Legitimation Crisis of Neoliberalism, 2017)
This chapter stresses the point that contrary to arguments proposed by neoliberals, the state has consistently been a relevant actor in the organization of the economy and society. It indicates that the role played by the state was fundamental in the expansion and stability of capitalism in its early stages, during the laissez-faire era of the nineteenth century and under Fordism in the twentieth century. This argument is illustrated through a review of salient aspects of classical liberal theories of the state such as those of John Locke, Adam Smith, Jeremy Bentham, and John Stuart Mill and a brief review of the theory of Marx and early twentieth century contributions such as those of Karl Polanyic and John M. Keynes. An analysis of the theories of the role of the state under Fordism is proposed in the final sections of the chapter.
Keywords: Fordism; MARX, Karl, 1818-1883; double movement; economic sociology; organizational studies; regulated capitalism

Nancy Fraser and Karl Polanyi. A Possible Dialogue - Brie, Michael (Karl Polanyi in Dialogue: A Socialist Thinker for our Times, 2017)
From the very beginning a misunderstanding has to be cleared up – the reduction of Polanyi’s work to that of a reformer who wants to counter the excesses of market radicalism with social protective measures and believes that the crisis of modern
Keywords: FRASER, Nancy; triple movement

The Labor of Informational Democracy: A Library and Information Science Framework for Evaluating the Democratic Potential in Socially- Generated Information - Cope, Jonathan (Progressive community action: Critical theory and social justice in library and information science, 2016)
This essay outlines a framework that LIS can use to analyze socially-generated information. The proposed evaluative framework involves three democratic horizons of analysis: the level of access, the level of production, and the level of communicative speech. This inquiry synthesizes the political economy of communication/librarianship, autonomist Marxist insights about the dematerialization of labor in late capitalism, and the concerns of contemporary democratic theory. The essay concludes with a set of proposals for LIS to pursue research and policies that use a critical theoretical framework linking the realm of production (i.e., labor) with communicative democracy.
Keywords: MARX, Karl, 1818-1883; dematerialization of labor; informational democracy; late capitalism

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Keywords: POLANYI, Karl, 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized

Singapore’s Social Contract Trilemma - Yeoh, Lam Keong; Auyong, Hawyee; Yeo, Andrew Zhi Jian (Globalization and Democracy in Southeast Asia, 2016)
The last 50 years of nation building has firmly established Singapore as a globally competitive and highly successful economy and city-state with one of the highest per capita incomes in the world. Singapore has achieved a prosperity undreamed of by its founders. How successfully Singapore can evolve into a fully developed nation, with a firm sense of national belonging, social cohesion, political legitimacy and participation—and not just a strong and successful developmental state—will depend on the extent to which the country is able to translate this success to broader social protection and democratic participation for her people, and the extent to which the country is able to forge a common national identity.
Keywords: FRASER, Nancy; Singapore; democracy; double movement; globalization; neo-Polanyian; policy studies; triple movement

The double movement and new labor market regulations in Korea, Japan, and Taiwan - Yun, Ji-Whan (A comparative study of East Asian capitalism, 2014)
Keywords: Japan; Korea; Taiwan; consolidation; diverging paths; double movement; dual labour markets; economics; labour; labour market reforms; politics and government; systemic change

Marxism After Polanyi - Burawoy, Michael (Marxisms in the 21st Century: Crisis, Critique and Struggle, 2013)
KM - What should we do with Marxism ? For most the answer is simple. Bury it ! Mainstream social science has long since bid farewell to Marxism. The approach adopted here is that Marxism is a living tradition that enjoys renewal and reconstruction as the world it describes and seeks to transform undergoes change ... However, Marxsm cannot simply mirror the world. It seeks to change the world, but changing such a variegated world requires a variegated theory that keeps up with the times and accommodates places.
Keywords: MARX, Karl, 1818-1883; Marxism; fictitious commodities

Port of trade - Möller, Astrid (The Encyclopedia of Ancient History, 2013)
A “port of trade” is a theoretical concept developed by Karl Polanyi (1886–1964) to describe the phenomenon of a particular kind of trading post.
Keywords: anthropology; economic history; multiculturalism

A Handbook of Economic Anthropology, Second Edition: Orientations: Karl Polanyi - Isaac, Barry L. (A Handbook of Economic Anthropology, Second Edition, 2012)
Keywords: capitalist systems; economic anthropology; economic history; economic sociology; history of economic thought: individuals; political economy; social and economic stratification

Understanding the “economization” of social formations - Jessop, Bob (The marketization of society: economizing the non-economic - Editors - Uwe Schimank, Ute Volkmann, 2012)
A critical review of nine dimensions of economization of social relations and their repercussions on societal dynamics. Discusses fictitious commodification, financialization, finance-dominated accumulation, and issues of ecological dominance. Bibliographic note: Book contains selected papers from conference on Marketization of Societies, organized at Bremen University, 1-2 June 2012. This is the pre-print version of a planned conference collection with a commercial publisher.
Keywords: fictitious commodification; fictitious commodities; financialization

Neoliberalism through the Lens of 'Embeddedness' - Paton, Joy (Neoliberalism: Beyond the Free Market, 2012)
Keywords: capitalist systems; history of economic thought: individuals; history of economic thought: macroeconomics; political economy

After Neoliberalism - Antonio, Robert J. (The Wiley-Blackwell Companion to Sociology, 2011)
This chapter contains sections titled: * Clashing Models of Capitalism: Hayek VS. Polanyi * Market Liberalism's Return: From the “Not Quite Golden Age” to the “Great U - Turn” * Hegemonic Neoliberalism: From Crest to Crisis to Emphatic Reassertion(?) * Capitalism at the Point of Inflection: Neoliberalism's Wake * Conclusion * References
Keywords: 2008 financial meltdown; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Hayek's and Polanyi's classic texts; New Deal; The Great U-Turn; ascendant neoliberalism; cutting edge issues; great recession; hegemonic culture; neoliberalism; neoliberalism's wake; self-regulating market

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Keywords: capitalism; emancipation; feminism; gender; welfare state

Adventures of an Austrian Trio Abroad: The Influence of Schumpeter, Polanyi and Hayek in Turkey and the Dissemination of Their Work - Ozveren, Eyup (The Dissemination of Economic Ideas, 2011)
Keywords: Austrian; Keynesian; Keynesianism; evolutionary; general aggregative models: Keynes; history of economic thought; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; post-Keynesian; role of economics; role of economists

From Menger to Polanyi: The Institutional Way - Cangiani, Michele (Austrian Economics in Transition, 2010)
The crisis of the institutions of liberal capitalism dates back to the last decades of the nineteenth century. Economics was thenceforth forced to radically reconsider its achievements and even its basic presuppositions, to the extent that they were linked to a free-market and perfect-competition model.
Keywords: economic history; economic systems; economic theory; financial economics; history of economic thought; international economics; macroeconomics; mathematical methods; methodology; monetary economics; quantitative economics

Concluding reflections on globalization(s) and labour in China and India: a Polanyian perspective - Harriss, John (Globalization and labour in China and India: impacts and responses., 2010)
Keywords: China; India; economics; globalization; labor; labour

Building the Human Economy Together - Hart, Keith; Laville, Jean-Louis; Cattani, Antonio (The Human Economy. A Citizen’s Guide, 2010)
KM: We want to bring to the attention of English readers some currents of economic theory and practice that have flourished in non-Anglophone countries over the last two decades, particularly in France, Brazil, Hispanic America and Scandinavia. To these we have added significant work by English-speaking authors that was sidelined during neoliberalism’s heyday and deserves to find a wider audience now. We have brought these strands of new thinking together under the umbrella concept of ‘the human economy’ which refers to an emphasis both on what people do for themselves and on the need to find ways forward that must involve all of humanity somehow.
Keywords: human economy; solidarity economy

The ordering of change: Polanyi, Schumpeter and the nature of the market mechanism - Harvey, Mark; Metcalfe, Stan (Markets, Rules and Institutions of Exchange, 2010)
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; market mechanism

The Financialization of Modern Economies in Monetary Circuit Theory - Pilkington, Marc (The Political Economy of Monetary Circuits: Tradition and Change in Post-Keynesian Economics, 2009)
Keywords: Canada: 1913-; banks; depository institutions; economic history: financial markets and institutions: United States; government and the monetary system; haute finance; history of economic thought: individuals; household saving; international financial markets; micro finance institutions; monetary policy, central banking, and the supply of money and credit; monetary systems; mortgages; payment systems; personal finance; regimes; standards

Markets Against Society: Labor's Predicament in the Second Great Transformation - Webster, Edward; Lambert, Robert (The ISA Handbook in Contemporary Sociology: Conflict, Competition, Cooperation, 2009)
Keywords: labour movement; northern compromise; second great transformation

Where Does the Market Come From? Why the Controversy Between Polanyi's "Substantivists" and "Formalist" Neoclassical Protagonists of a Universal Market Was Never Solved" - Heinsohn, Gunnar (Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy, 2008)
In Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy - Metropolis-Verlag, 2008.
Keywords: formalist; substantivist

Third Sector, Social Economy, Civil and Solidarity-Based Economy: European Reality and Theoretical Debate | - Laville, Jean-Louis (2008)
This is a book chapter from: The Social Generative Action of the Third Sector – Comparing International Experiences Edited by H. K. Anheier; G. Rossi, L. Boccacin, 2008, Vita e Pensiero, Milano
Keywords: social economy; solidarity economy

The Politics of Liquid Modernity: Polanyi and Bauman on Commodification and Fluidity - Christodoulidis, Emilios (Liquid Society and Its Law, 2007)
Book edited by Jirí Pribán This collection of essays brings together Zygmunt Bauman and a number of internationally distinguished legal scholars who examine the influence of Bauman's recent works on social theory of law and socio-legal studies. Contributors focus on the concept of 'liquid society' and its adoption by legal scholars. The volume opens with Bauman's analysis of fears and policing in 'liquid society' and continues by examining the social and legal theoretical context and implications of Bauman's theory.
Keywords: BAUMAN, Zygmunt; commodification; fluidity; law / jurisprudence; liquid modernity; philosophy; political philosophy

The Political Economy of Mesoamerican States: An Economic Ethnographer's View - Halperin, Rhoda (The Political Economy of Ancient Mesoamerica: Transformations During the Formative and Classic Periods, 2007)
KM: outlines a generic model of political economy based on Polanyi's writings and explores some of its implications.
Keywords: Mesoamerica; economic anthropology

The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Reading Karl Polanyi for the Twenty-First Century, 2007)
The postwar reconstruction of domestic and international orders ushered in a new political economy of capitalism. It entailed a far-reaching reorganization of social relations and economic institutions and accorded to the state an important role in the management of the economy. Many of the institutions of classical liberalism were displaced by interventionist mechanisms. The welfare state consolidated and extended multifarious forms of protection accorded to labor. A new level of labor-market regulation and public provisioning transformed the conditions under which people worked and lived, leading to higher incomes for large groups of society, and creating a higher degree of security for them both in the workplace and beyond. International institutions were created to facilitate the regulatory functions that these welfare states had assumed, supported by a conducive exchange-rate regime and restrictions on capital mobility.
Keywords: capital mobility; market society; market system; postwar period; postwar reconstruction; welfare state

Karl Polanyi on the Limitations of Formalism in Economics - Stanfield, James Ronald; Carroll, Michael C.; Wrenn, Mary V. (Choice in Economic Contexts, 2006)
This chapter examines Karl Polanyi's critique of formalism in economics and his case for a more institutional economics based upon a reconstitution of the facts of economic life on as wide an historical basis as possible. The argument below reviews Polanyi's argument with regard to the relation between economic anthropology and comparative economics, the contrast between the formalist and substantive approaches to economic analysis, the notion of an economistic fallacy, the most important limitations of the conventional formalist economics approach, and the nature and import of the new departure that Polanyi envisioned. James Ronald Stanfield, Michael C. Carroll, Mary V. Wrenn (2006), Karl Polanyi on the Limitations of Formalism in Economics, in Donald C. Wood (ed.) Choice in Economic Contexts (Research in Economic Anthropology, Volume 25) Emerald Group Publishing Limited, pp.241 - 266
Keywords: economic anthropology; formalism

Globalization - McMichael, Phillip (The Handbook of Political Sociology states, civil societies, and globalization, 2005)
Philip McMichael casts a critical eye on the process of globalization suggesting that it takes different forms across time and space. He specifies contemporary globalization as a discursive project, geared to institutionalizing corporate markets through multilateral and regional economic agreements driven by powerful states. From this perspective of depicting globalization as an exercise in power, he examines political countermovements to globalization. Global justice movements, he argues, are globalization’s “historical and relational barometer,” and they operate at various, but often interrelated, scales. Work- ing from Karl Polanyi’s “double movement” of implementation of and resistance to economic liberalism, McMichael questions the adequacy of Polanyi’s formulation for the elaboration of market rule in the twenty-first century. This question concerns the conventional interpretation of “sovereignty” as the centerpiece of nation-state formation, including the development of citizenship. Here, globalization is viewed through the lens of a sovereignty crisis, where corporate market rule compromises the social contract upon which the state/citizen relation is founded. The crisis is expressed differently across the world, as the impact of market rule generates alternative social movement conceptions of sovereignty, especially in the global south where corporate globalization is realized through a drastic intensification of social exclusion.
Keywords: counter-movement; critique; double movement; globalization; political sociology

Karl Polanyi as a Development Economist - Polanyi Levitt, Kari (Pioneers of Development Economics: Great Economists on Development, 2005)
The history of modern economic thought has been pre-occupied with the question of economic transformation or development. This survey of important contributions to the economics of development includes many economists not normally considered as pioneers in this field. The contributors point to the role of imperialist considerations in the early development of economic thought and the development discourse, and the impact of pressures for social and political reform. The economists and thinkers discussed include William Petty, David Ricardo, Friedrich List, Alexander Hamilton, Karl Marx, Vladimir Ilyich Lenin, Alfred Marshall, Michal Kalecki, John Maynard Keynes, Nicholas Kaldor, Karl Polanyi, Raul Prebisch, Arthur Lewis, Alexander Gerschenkeron and Hans Singe
Keywords: development economics; economic history

Social Embeddedness. Within Political Economy: The Work of Karl Polanyi - Watson, Matthew (Foundations of International Political Economy, 2005)
BOOK ABSTRACT: Despite a burgeoning debate on substantive issues in IPE, little attention has been devoted to its theoretical foundations. In this important new text, Matthew Watson reviews the main current theoretical approaches to IPE and highlights the problems that arise from treating 'states' and 'markets' as separate and contesting units of analysis. Foremost among these problems is the lack of attention given to theorizing the constitution of the individual as both an economic agent and a moral being.
Keywords: international political economy; social embeddedness

Global liberalism, environmentalism and the changing boundaries of the political: Karl Polanyi's insights - Meyer, J.M. (Environmental Values in a Globalizing World: Nature, Justice and Governance, 2004)
Keywords: environmentalism; global liberalism

Economic Rationality and Globalization: A Feminist Perspective - Beneria, Lourdes (Feminist Economics Today: Beyond Economic Man, 2003)
KM: a section focuses on Polanyi's analysis of the social and political construction of markets and of "market society" in Europe, and then discusses the extent to which this type of analysis can be applied to the formation of global markets in the late twentieth century. It then looks at gender dimensions and the tension between the assumptions of economic rationality associated with market behaviour and the real-life experiences of women and men. Beneria then extends this analysis to the effects on women of globalization and the feminization of the labour force.
Keywords: feminism; feminization of labour force; gender; globalization; market society

Chapter 7: Karl Polanyi - Rogerson, Kenneth S.; May, Christopher (Key Thinkers for the Information Society, 2002)
This article presents Karl Polanyi's analysis of the dynamic relationships between economy and society in the information age. Of the many concepts Karl Polanyi provides in his analysis of economic relations, three stand as carefully calculated assumptions about the relationship between society and economy: the embeddedness of information in society, the commoditization of information and the existence of a double movement in the information revolution. Information has always been embedded in societal interactions. To emphasize this point, he said that the simple flow of information seems to have little effect in and of itself on the outcome of social interchanges. In Polanyi's words, it is also embedded in other social relations, such as political, economic, cultural, or health-related discussions and actions. On the issue of information commoditization, Polanyi takes a different view. His logic indicates that there will be negative social consequences associated with it. One example is digital divide or the discrepancies on a global or national level between those who have access to information through new technologies and those who do not. With regards to the existence of double movement, Polanyi believed that there are two opposing forces-economic liberalism and social protection-present during the industrial revolution. However, this is not easy to see in the information age because of simple paradox. First, people who would eschew the uses of technology for ideological reasons,may turn to it for other reasons. And second, there is only a protest of a specific issue and not the imbalance of information flows or the ownership of information dissemination methods.
Keywords: commercialization; communication revolution; digital divide; industrial revolution; information technology; liberalism

The Great Depression and the Decline of Liberal Capitalism: Polanyi and Schumpeter - Trigilia, Carlo (Economic Sociology, 2002)
This chapter contains section titled: * Market Domination and Society's Self-Defense * The Decline of the Bourgeoisie and Anti-Capitalist Policies * Analytical Convergence and Political Divergence
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; capitalism; depression; economic level; economic sociology; international relations; social conditions

Chapter 6: Our time - Heiskala, Risto (Will Europe Work?, 2001)
The article focuses on Europe in the age of global networks and flowing identities. In the article the author discusses the articulation of Europe. He starts with a discussion on the identity of Europe, goes on with a discussion of globalization and closes with an attempt to tie these two themes together. He then raises, in a new context, sociologist Karl Polanyi's question: "What Kind of a Time Is Our Time?" Throughout the article, specific emphasis is put on the European Union, as this network state currently uniting fifteen and in the nearest future possibly twice as many European states as today is often what is referred to combined with the term "Europe", even if it would be a mistake to believe that these two are identical. The article also throws light on the affect of Islam on the countries of Europe. In several European countries there are enclaves of millions of Muslim migrant workers and there are Muslim countries at the borders of Europe in North Africa and the Middle East.
Keywords: Europe; Islam; globalization; identity (philosophical concept); immigrants

Karl Polanyi and the creation of the "market society" - Gootenberg, Paul (The other mirror : grand theory through the lens of Latin America (Edited by Centeno, Miguel Angel, López-Alves, Fernando)., 2001)
Keywords: Latin America; economic history; philosophy; politics and government; social sceinces

Karl Polanyi's Great Transformation and the Current Transformations in Central Europe - Hake, Eric R.; Neale, Walter C. (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Keywords: agriculture; collectives; communes; comparison of public and private enterprises and nonprofit institutions; contracting out; economic thought; history of economic thought: individuals; illegal behavior; legal institutions; nonprofit institutions; privatization; public enterprises; socialist systems and transitional economies: legal institutions; transitional economies

Contesting the "Great transformation" : local struggles with the market in South India - Herring, Ronald (Agrarian studies : synthetic work at the cutting edge, ed. by James C. Scott and Nina Bhatt, 2001)
Keywords: India; agrarian studies

Groundwork for an Institutional Economic Approach to 'Transition': Smith and Polanyi Reconsidered - Ozveren, Eyup (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Keywords: Marxist; SMITH, Adam, 1723-1790; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought through 1925: socialist; history of economic thought: classical; history of economic thought: individuals; socialist systems and transitional economies: performance and prospects P27

What Karl Polanyi Found in Dahomey - Sandall, Roger (The culture cult : designer tribalism and other essays, 2001)
A study of the social effects of romantic primitivism.
Keywords: alternative lifestyles; culture; meningen; modern civilization - public opinion; primitive societies - public opinion; primitivism

Conceptualizing Resistance to Globalization - Chin, Christine B. N.; Mittelman, James H. (Globalization and the Politics of Resistance, 2000)
Assessments of resistance to globalization are necessarily influenced by the manner in which one conceptualizes these processes. Too often, both of the terms (‘resistance’ and ‘globalization’) are used promiscuously, the latter as a buzzword or catchall and the former in many different ways, sometimes as a synonym for challenges, protests, intransigence, or even evasions. Hence, we seek to juxtapose alternative explanations of resistance and highlight the complexities of conceptualizing it. The purpose of this chapter, then, is to explore the question, what is the meaning of resistance in the context of globalization?
Keywords: Islamist movement; NAFTA; globalization; international political economy; organic intellectual; resistance; symbolic resource; transnational capital

Market Dominance, Crime, and Globalisation - Messner, Steven F.; Rosenfeld, Richard (Social Dynamics of Crime and Control: New Theories for a World in Transition, 2000)
KM: Our point of departure is Karl Polanyi's classic work on the emergence of industrial capitalism and recent studies that further develop Polanyi's insights. We draw on these analyses to pose a fundamental issue confronting all capitalist societies: the need to restrain the market and prevent the economy from dominating other institutional realms. We explain how this general institutional challenge bear specifically on the problem of crime and crime control
Keywords: crime; double movement; globalization; institutional-anomie theory; law

Polanyi and social economy - Isaac, Barry L. (A Handbook of Economic Anthropology, 2022)
Substantivism stemmed from the writings of Hungarian lawyer-turned-historian Karl Polanyi, who argued that capitalism is a historically unique kind of economy that is disembedded from the social matrix. By implication, the socially embedded pre-capitalist economies studied by anthropologists, historians and classicists cannot be understood using the formal economics developed to analyze capitalist economies. Rather, new tools for analysing their 'substantive' economies must be employed. Substantivism was championed in economic anthropology by economist-turned-anthropologist George Dalton and became the reigning paradigm in the subfield during the 1960s. Formalism arose in opposition, arguing that capitalist and pre-capitalist economies differ in degree, not in kind, and thus can all be analysed using the tools of microeconomics. Formalism largely displaced substantivism during the 1970s and 1980s as anthropologists increasingly focused on the economic integration of the world's peasant sectors into their national and regional economies.

Capitalism and Crisis: Thinking Through Capitalist Crisis with Schumpeter and Polanyi - Delanty, Gerard (Capitalism, Democracy, Socialism: Critical Debates, 2022)
The chapter offers an analysis of capitalist crisis through a reading and discussion of two seminal texts on capitalism, Joseph Schumpeter’s Capitalism, Socialism and Democracy [1943] and Karl Polanyi’s The Great Transformation [1944]. These inspiring works on economic history and social theory offer profound insights into the nature of capitalist crisis. Although written in the mid-twentieth century many of the insights in these books are of relevance to the current situation as capitalism undergoes another revulsion. While the two authors were very different – Polanyi a left-wing critic of capitalism; Schumpeter a politically right-wing economist who favoured capitalism – both were influenced by Marx’s analysis of capitalism and have helped to shape the debate on the crisis of capitalism. Indeed, Schumpeter was convinced Marx was mostly right in his prediction of the end of capitalism and the triumph of socialism. The chapter begins with a brief account of the Marxist theory capitalism in order to contextualise the discussion of the two theorists.
Keywords: MARX, Karl, 1818-1883; Polanyi; SCHUMPETER, Joseph Alois, 1883-1950; capitalism; crisis

Market society and the institutional theory of Karl Polanyi - Cangiani, Michele (Institutional Economics: Perspectives and Methods in Pursuit of a Better World, 2021)
This chapter examines Polanyi’s institutional theory of market-capitalist society. It shows that market society is, according to Polanyi, a peculiarly “economic” society: its economy appears both autonomous and dominant, constraining the structure and evolution of other social subsystems. The chapter also demonstrates that Polanyi’s theory and method allow an explanation of the institutional transformations of market society. In the face of today’s great economic difficulties, social uneasiness, and ecological distress, Polanyian institutionalism remains a rich source of insight on humanity’s challenges and possibilities.

Going public with Polanyi in the era of Trump * - Burawoy, Michael (The Routledge International Handbook of Public Sociology, 2021)
After considering different possible elements of the ‘Trump era,’ I will turn to The Great Transformation to periodize capitalism into three waves of marketization and their counter-movements. In the first wave, we follow the commodification of land, money and especially labor, so-called fictitious commodities, and the local counter-movements marketization inspired, reaching to the level of the state. In the second wave, the focus turns on the way marketization generated a reaction from states, seeking to regulate commodification – in other words, processes of de-commodification. Given the tension between capitalism and democracy, in Polanyi’s view essentially two forms of regulation were possible: either democracy suppresses capitalism and we get socialism, or capitalism suppresses democracy and we get fascism. He neither paid much attention to the popular forces that led in either direction nor to the possibility of a compromise between capitalism and democracy that reigned in three decades after World War Two. Beginning in the 1970s, we witnessed the beginning of a third wave of marketization – more commonly known as neoliberalism – that Polanyi did not anticipate. I attribute his failure to anticipate another wave of marketization to the contradictory pressures of accumulation that are temporarily alleviated by commodification. In this third wave, I show how democracy is discredited, and consensus politics dissolves into polarizing movements within and beyond parliamentary politics. The lived experience driving these movements, I argue, revolves around processes of re-commodification and ex-commodification of nature, money, labor and knowledge. This is the terrain upon which sociology must engage its publics. I highlight two approaches, both founded on an organic public sociology that engages directly with publics. On the one hand, there is the empathic public sociology that wades into communities in order to comprehend the distinctive ‘deep narrative’ of right wing populism, typified by Arlie Hochschild’s Strangers in Their Own Land. On the other hand, there is the affirmative public sociology that creates a collective vision based on a dialogue with the practitioners of real utopias, typified by Erik Wright’s How to Be an Anti-Capitalist in the Twenty-First Century.
Keywords: Trumpism; marketization; public sociology

Ecology, Democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Ryan, J. Michael (COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the ethics and ideologies, inequalities, and changed social understandings that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities – both positive and negative – that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume II: Social Consequences and Cultural Adaptations, are the result of the collaboration of more than 50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
Keywords: COVID-19; disease & health Issues; health

This freedom kills: Karl Polanyi’s quest for an alternative to the liberal vision of freedom - Brie, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reconstructs the emergence and formulation of Karl Polanyi's central research question: How is responsible freedom possible in a complex modern society? The origins of this question in the time before the First World War and the confrontations with the challenge of neoliberalism and fascism are discussed. It is shown that Karl Polanyi's concept of freedom has four dimensions. Polanyi connects negative, positive, substantial and social freedom with each other and formulates a highly innovative research programme which forms the basis for The Great Transformation and later works.
Keywords: freedom; freedom in a complex society

Commodified money and crustacean nations - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
Though Polanyi referred to three distinct fictitious commodities, one, money, and the fate of the apex structure that commodified it, the gold standard, structured The Great Transformation’s narrative. Despite this centrality of money and its commodification to Polanyi’s masterwork, there is near-deafening silence in Polanyi scholarship on money as a fictitious commodity. This chapter ends it. It traces Polanyi’s understanding of fictitious commodities to its sources in classical political economy and explains how the near total dominance of the antithetical tradition of neoclassical economics obscures understanding. The chapter also argues that the resulting argument shared a great deal with the classical Marxist theories of imperialism and of uneven and combined development of previous decades, particularly their arguments about the centrality of powerful nation states to capitalism. It stresses another hitherto neglected aspect of Polanyi’s argument, that the double movement led to the emergence of ‘crustacean nations’. As such, the chapter argues, The Great Transformation contributes a great deal towards a new approach to understanding world affairs, geopolitical economy, which challenges Ricardian ‘universalist’ understandings and takes the ‘materiality of nations’ seriously. It, and Polanyi, are more relevant than ever in our ‘deglobalizing’ age of multi-polarity.
Keywords: Marxism; fictitious commodities; imperialism; money

Introduction: Karl Polanyi in the twenty-first century - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
This introduction places the contributions that follow in the context of Polanyi’s rising influence, its causes and effects, and of the key twenty-first century developments that make his oeuvre more relevant than ever. It emphasizes how the contributions push the boundaries of received understandings of Polanyi. While some contributions fill gaping holes, such as those on money as a fictitious commodity, others overturn received understandings, whether that of the double movement or fictitious commodities, or the provenance (Central European or American) of his principal ideas and concerns or how he understood socialism. Yet others demonstrate how amenable Polanyi’s ideas are to further development. Last but not least, the introduction outlines Polanyi’s historical diagnosis as it emerges from these innovative contributions and argues that the stark choice he felt faced European societies, socialism or fascism, is once again before us as we face the groundswell of nationalist and far right forces.
Keywords: capitalism; contemporary relevance; fascism; socialism

Double movement, embeddedness and the transformation of the financial system - Galarza, Oscar Ugarteche (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reviews aspects of the possible transformation of the financial system into a banking complex, that comprises both embedded Too Big to Fail (TBTF) financial institutions and disembedded ones. The transformation of the financial system into a two-tier banking complex is the result of the disconnection of the TBTF embedded institutions and the right size to fail disembedded financial institutions. The chapter revises the scope and consequences of this change on the monopolization of financial capitalism and international financial governance. It contains two sub-sections. The first reviews Polanyi’s concept of embeddedness/ disembeddedness and TBTF; the second reviews the concept of a complex. This chapter aims to use Polanyi’s concept of embeddedness and disembeddedness in order to understand how the category of TBTF financial institutions came into being through the double movement of market deregulation and social regulation. The concepts of embeddedness in social regulation and disembeddedness under market regulation permit an understanding of how, as the few TBTF financial institutions re-embedded themselves, becoming risk proof, the majority remained disembedded and subject to failures. We argue that, given this, the financial system may no longer be considered a system.
Keywords: disembeddedness; double movement; embeddedness; financial system; too big to fail

Debt, land and money: From Polanyi to the new economic archaeology - Hudson, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
Polanyi spoke of the commodification of money, and this chapter focuses on how interest-bearing debt became the major dynamic, also contributing to the commodification of land and labor. By the late third millennium BC the main way to obtain manual labor was to lend money and make debtors work off their debts as an antichretic interest charge. Personal debt became the lever for creditors to pry land out of the clan-based tenure system, mainly for sale under economic duress. Debtors who pledged their crop or land rights usually ended up forfeiting them. This alienation catalyzed the ‘commodification’ of land. By tracing these debt dynamics, the new economic archaeology is compatible with Polanyi’s intuitions and recognition that market relations are embedded in social relations, and extends his analysis in tracing how administered pricing and monetary valuations created the preconditions for market exchange. The earliest markets, credit and land tenure systems were regulated. Administered pricing was a precondition for creating weights, measures and price equivalencies to enable market exchange to evolve more flexibly.

Multilinear trajectories: Polanyi, The Great Transformation and the American exception - Lacher, Hannes (Karl Polanyi and twenty-first-century capitalism, 2020)
Karl Polanyi’s call, in The Great Transformation, for a re-embedding of markets, is widely understood to have come to fruition in the American New Deal and in the post-war order of ‘embedded liberalism’. Based on archival sources, this chapter shows that Polanyi’s political project was far more radical. Polanyi initially considered the New Deal a vital response to the problems of American capitalism, but one that would have little relevance to the problems and dynamics of European societies. There, he considered a socialist transformation both possible and necessary. But eventually, Polanyi realised that the US, far from remaining an exceptional outlier of ‘nineteenth-century civilisation’, was imposing its model on Britain and Europe. The internationalisation of the American New Deal in the Bretton Woods order marked the defeat of Polanyi’s political project.

Polanyi in space - Peck, Jamie (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter addresses the potential of Karl Polanyi’s contribution as a spatial theorist, or as an economic geographer in all but name. Although Polanyi did not identify as a spatial or geographical theorist as such, his work is rich with spatial insights and implications, notably as one of the original analysts of economic diversity. The chapter begins by contextualising Polanyi’s work in relation to the shifting locales and vantage points that shaped its production. It then turns to the question of the potential of Polanyi’s research programme (incomplete as it understandably was) for the conceptualisation and exploration of economic geographies. The goal here is to sketch some of the ways in which neoPolanyian approaches can be put to work in the service of geographically sensitive modes of economic inquiry, including those attuned to the ongoing diversity of economic formations and development trajectories, contemporary engagements with uneven spatial development, and the evaluation of (localised) economic experimentation. Polanyi’s programmatic project of ‘comparative economics’ was never completed during his own lifetime. There is much to be gained from resuming this project.

The reality of society - Rotstein, Abraham (Karl Polanyi and twenty-first-century capitalism, 2020)
In these remarkably stirring reflections, delivered at the 2014 conference from which most of the contributions to this volume emerge, the late Abe Rotstein, Polanyi’s student and collaborator, recalls the projected sequel to The Great Transformation, to be titled Freedom and Technology. Whereas the former was built on a social sciences approach using institutional analysis, the sequel was to follow the intention Hegel expressed in the words ‘Wir die religiöse Vorstellung in Gedanken fassen’ (We want to turn religious expression into philosophical thought). Polanyi took religion seriously – not its outer ceremonial trappings but the important truths that lay behind and beneath these beliefs and practices. The sequel was to trace humanity’s progression through three major revelations: the knowledge of death, the discovery of our inner life and conscience, and the realization of freedom amid our social obligations. This was the idea of ‘the reality of society’ around which the whole book was to be built. It was the precursor of our cherished civil freedoms and closely connected with Polanyi’s idea of freedom in a complex society; it is also deeply threatened in an age of state and corporate cyber surveillance.
Keywords: freedom; reality of society; technology

Polanyi’s democratic socialist vision: Piketty through the lens of Polanyi - Somers, Margaret R.; Block, Fred (Karl Polanyi and twenty-first-century capitalism, 2020)
This chapter brings Karl Polanyi into dialogue with Thomas Piketty, author of Capital in the Twenty-First Century. The dialogue is intended to make visible key aspects of Polanyi’s theoretical framework while also suggesting limitations in Piketty’s approach to political economy. Specifically, the authors use the concept of ‘predistribution’ – implicit in Polanyi – to critique Piketty’s emphasis on redistribution as the solution to growing wealth and income inequality. Predistribution conveys the idea that the initial market distribution of income is not natural but is shaped by the systematic exercise of political and economic power.

Fictitious ideas, social facts and the double movement: Polanyi’s framework in the age of neoliberalism - Thomasberger, Claus (Karl Polanyi and twenty-first-century capitalism, 2020)
In the last decades, Karl Polanyi has gained recognition as one of the most important social scientists of the twentieth century. His seminal book, The Great Transformation, is listed among twentieth- century classics. How can this book, written more than seventy-five years ago, be applied to the current conditions? In order to answer this question the chapter not only compares the civilization of the nineteenth century in Europe with our own epoch. It also reconstructs some of Polanyi’s most important insights, such as his critique of the liberal utopia (in its classical and neoliberal version), his interpretation of the double movement, his vision of the meaning of the industrial revolution, his understanding of the problem of freedom in a complex society and his idea of a necessary ‘reform of human consciousness’. The chapter closes with a discussion of the question of how Polanyi’s categories can be used fruitfully so as to throw light to the post-war era and our society today.
Keywords: Great Transformation, The (Book); double movement; freedom in a complex society; liberal utopia; social facts

Understanding the (Re-)regulation of Private Renting in England: Karl Polanyi, the Rogue Landlord, the Responsible Tenant and the Decent Home - Carr, Helen; Alcock, Rowan (Contract law and the legislature: Autonomy, expectations, and the making of legal doctrine, 2020)

Ecology, democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Duzgun, Eren (Ecology, democracy, and COVID-19, 2020)
This chapter argues that Karl Polanyi’s economic sociology offers foundational concepts for a radical analysis of the social and ecological conditions that have caused the coronavirus pandemic. Furthermore, it shows that Polanyi’s work, often claimed for social democracy, has the potential to provide much more radical insights into the question as to how to “re-embed” our economies, thereby leading to a fundamental rethinking about the ways in which the present crisis can be overcome.
Keywords: COVID-19

The Specter of the 1930s in Asian Nation-Building: Global Fascism, Colonial Biopolitics, and the Origins of Modern Asia - Lee, Alex Taek-Gwang (Back to the ‘30s? : Recurring Crises of Capitalism, Liberalism, and Democracy, 2020)
An analysis of the connection between fascism and biopolitics in modernizing East Asia reveals that fascism served as colonial biopolitics, and was not historically specificity to Europe, though the rise of fascism was central to European colonialism and its technology of governance. As the last stage of capitalism, imperialism came with an expansion of social engineering in colonial countries, forcing colonized peoples to be “civilized.” I challenge the understanding of European fascism, arguing that fascism is inseparable from colonial biopolitics by analyzing non-European experiences in the 1930s. East Asia was then a site in which fascism, premised on building a utopian nation-state, played a pivotal role in encouraging people to insist upon political and economic autonomy in order to compete with Europe. The Manchurian Empire (滿州帝國) was an attempt to realize this utopian idea of fascism. Finally, I argue that these fascist experiences remain influential in the region and constitute a mirror image of European modernity.
Keywords: Japanese Fascism and Imperialism; Japanese colonialism; Manchukuo, history and politics; biopolitics of colonialism; fascism; nationalism and nation-building in East Asia

Where are markets? - Peck, Jamie (Market/Place: Exploring Spaces of Exchange, 2020)
The goal of this chapter is to prepare the ground for theorizing the diversity and spatiality of markets, (necessarily) dealing with, but seeking to move concertedly beyond, the restrictive optic of the orthodox model. It seeks to do so by way of three steps. The following section opens up some preliminary questions about the place of markets and their actually existing historical geography. Next, the chapter turns to the challenge of decentring the market, of moving beyond the idea that the market properly and eternally belongs at the centre of the economic universe. What is the scope for understanding “real markets”, both conceptually and empirically, without recourse to the idealized model of the “pure” market, and all its downstream distortions? Finally, the chapter addresses the question of alternative “mappings” of markets, taking some cues from the work of Karl Polanyi, but urging a more thoroughgoing reconstruction. The chapter’s conclusion acknowledges that the “where?” of markets remains a demanding theoretical question, such that what follows serves to inform some different points of departure, not the destination itself. New answers to this “where?” question, though properly a matter for what Polanyi characterizes as the “substantivist” investigation of real-world market formation, re-formation and transformation, ought to recognize, inter alia: first, the relational character of markets, which are codependent on non-market modes of coordination and regulation; second, their “instituted” form, necessary in function but variable in practice; and not least, third, their always out-of-equilibrium processual dynamics and contradictions.
Keywords: markets; space

Introduction : exploring markets - Peck, Jamie; Berndt, Christian; Rantisi, Norma (Market/Place: Exploring Spaces of Exchange, 2020)
The origin of the present volume was an invitational workshop focused on questions of the spatiality and diversity of markets, held at the Karl Polanyi Institute of Political Economy in Montreal in the summer of 2017. This was an apt meeting place in a more than literal sense. Although many of those in attendance did not subscribe explicitly to a Polanyian worldview or mode of analysis, most had engaged with Polanyi’s work in different ways. Some had made extensive contributions to neo-Polanyian scholarship, while others were more closely affiliated to radical political economy, performativity approaches or poststructuralism. In this context, more pertinent were a series of broadly aligned sympathies with what might be characterized as Polanyian dispositions, including: shared recognition of the importance of respectful, constructive and non-dogmatic exchange across an interdisciplinary range of heterodox and critical positions; overlapping concerns with the potential of empirically engaged and “substantivist” investigation (to borrow the Polanyian terminology), not just in testing and tweaking extant theories but in the construction of new insights, understandings and socio-political visions; and mutual commitments to humane, emancipatory and sustainable modes of socio-economic and ecological development.
Keywords: Karl Polanyi Institute of Political Economy; economic geography; markets